Magazine Picture Collage in Group Supervision - Shepard, Blythe C.; Guenette, Francis L. (Canadian Journal of Counselling and Psychotherapy, 2010)
A magazine picture collage activity was used with three female counsellor education students as a vehicle to support them in processing their experience as counsellors in training. The use of magazine picture collage in group supervision is described, and the benefits and challenges are presented. The collages served as jumping-off points for group discussions on developing a sense of competency, a quest for answers, discovering their strengths, finding personal and professional balance, and moving towards the realities of the counselling profession. Collage work can provide an alternate medium in supervision to develop reflective analysis and self-exploration.